Biodiversity is the key to food security - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Loss of biodiversity has been identified as one of the main obstacles to sustainable development. In the remote Pacific region, it has a special resonance, posing a tangible threat to the health and livelihoods of island communities.